Colonisation of Irish patients with chronic obstructive pulmonary disease by Streptococcus pneumoniae and analysis of the pneumococcal vaccine coverage: a non-interventional, observational, prospective cohort study. Issue 7 (9th July 2017) - McCarthy, Hannah; Jackson, Mandy; Corcoran, Mary; McElligott, Martha; MacHale, Elaine; Sulaiman, Imran; Cushen, Breda; Costello, Richard W; Humpreys, Hilary
Abstract : Objectives: To characterise the pattern of colonisation and serotypes of Streptococcus pneumoniae among patients with chronic obstructive pulmonary disease (COPD) who currently receive the 23-valent pneumococcal polysaccharide vaccine (PPV-23) according to vaccination status, use of antibiotics and steroids. To investigate the prevalence of PPV-23 and 13-valent pneumococcal conjugate vaccine (PCV-13) serotypes within the study cohort. Design: A non-interventional, observational, prospective cohort study with a 12 -month follow-up period inclusive of quarterly study visits. Setting: Beaumont Hospital and The Royal College of Surgeons in Ireland Clinical Research Centre, Dublin, Ireland. Participants: Patients with an established diagnosis of COPD attending a tertiary medical centre. Primary outcome measure: Colonisation rate of S. pneumoniae in patients with COPD and characterisation of serotypes of S. pneumoniae with correlation to currently available pneumococcal vaccines. Sputum and oropharyngeal swab samples were collected for the isolation of S. pneumoniae . Secondary outcome measure: Seasonality of colonisation of S. pneumoniae and its relationship with the incidence of exacerbations of COPD. Results: S. pneumoniae was detected in 16 of 417 samples, a colonisation incident rate of 3.8% and in 11 of 133 (8%) patients at least once during the study. The majority of S. pneumoniae isolates were identified in spring and were non-vaccine serotypes for either the PPV-23 or PCV-13 (63%). The colonisation incident rate of S. pneumoniae fluctuated over the four seasons with a peak of 6.6% in spring and the lowest rate of 2.2% occurring during winter. Antibiotic use was highest during periods of low colonisation. Conclusions: There is seasonal variation in S. pneumoniae colonisation among patients with COPD which may reflect antibiotic use in autumn and winter. The predominance of non-vaccine types suggests that PCV-13 may have limited impact among patients with COPD in Ireland who currently receive PPV-23. Trial registration number: NCT02535546; post-results.